Transaction Costs and Agricultural Household Supply Response of Maize Farmers in Ogbomoso Agricultural Zone of Oyo State - Oladejo, J. A. (International Journal of Bio-resource and Stress Management, 2010)
This research was an attempt to determine the magnitude and the direction to which the level of transaction costs influence changes in maize supply in the study area. Multi-stage random sampling technique was employed to select 110 maize producing farmers for the study. Data for the study were collected using structured interview schedule and analyzed using descriptive statistics and estimation of Cobb-Douglas regression model. The result showed that mean age for respondents was 45.8 years while more than half of them were literates. The major source of finance for the farmers was personal savings while the mean land area cultivated was 2.1 ha. The results of the regression analysis showed that significant relationships exist between transaction costs and agricultural household supply response in the study area. The average fixed and proportional transaction costs were N 2960.82 and N 15906.58, respectively.